Effect of SP600125 on proliferation of embryonic stem cell - Zhou, Yonghua; Jiang, Minggui; Wang, Mei; Luo, Chao; Wang, Zili; Wen, Sheng; Liu, Wenbin; Xiao, Yamei (Scientific Research Publishing, 2013)
SP600125 is an inhibitor of c-Jun NH2-terminal kinase (JNK), which plays a fundamental role in regulating animal development. Using SP600125 to deal with the mouse embryonic stem cells, it is revealed that the number of the ESC colonies decreased and the size became smaller. With treatment by SP600125, the proliferation of mouse ES cells is seriously inhibited for the cycle arrested in the G2/M phase, and the effect of SP600125 on the ES cells displays correlation of dose and time. The obtained results indicate that JNK may be an important regulator in the progression of cell cycle at the G2/M cell phase for the ES cells.
Keywords: JNK; SP600125; Embryonic Stem Cell; Cell Cycle